Entanglement universality of two-qubit X-states - Mendonca, Paulo E. M. F.; Marchiolli, Marcelo A.; Galetti, Diogenes [UNESP] (Elsevier B.V., 2014)
We demonstrate that for every two-qubit state there is a X-counterpart, i.e., a corresponding two-qubit X-state of same spectrum and entanglement, as measured by concurrence, negativity or relative entropy of entanglement. By parametrizing the set of two-qubit X-states and a family of unitary transformations that preserve the sparse structure of a two-qubit X-state density matrix, we obtain the parametric form of a unitary transformation that converts arbitrary two-qubit states into their X-counterparts. Moreover, we provide a semi-analytic prescription on how to set the parameters of this unitary transformation in order to preserve concurrence or negativity. We also explicitly construct a set of X-state density matrices, parametrized by their purity and concurrence, whose elements are in one-to-one correspondence with the points of the concurrence versus purity (CP) diagram for generic two-qubit states. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Entanglement; Concurrence; Negativity; Relative entropy of entanglement; X-state